2019
DOI: 10.1093/neuros/nyz041
|View full text |Cite
|
Sign up to set email alerts
|

Is Admission Lipoprotein-Associated Phospholipase A2 a Novel Predictor of Vasospasm and Outcome in Patients With Aneurysmal Subarachnoid Hemorrhage?

Abstract: BACKGROUND The relationships between lipoprotein-associated phospholipase A2 (Lp-PLA2) level, vasospasm, and clinical outcome of patients with aneurysmal subarachnoid hemorrhage (aSAH) are still unclear. OBJECTIVE To identify the associations between admission Lp-PLA2 and vasospasm following subarachnoid hemorrhage and the clinical outcome of aSAH. METHODS A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…The average number of patients with aSAH who were admitted to our hospital per month during the COVID-19 pandemic was not significantly different from that in the previous report (17 patients/month vs. 17.9 patients/month). 17 No patient with posterior circulation aneurysm underwent clipping in this cohort. A pterional keyhole approach was used except in 3 patients who developed brain herniation and received classic decompressive hemicraniectomy (1 [5%] vs. 2 [4.8%]; P = 0.967).…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…The average number of patients with aSAH who were admitted to our hospital per month during the COVID-19 pandemic was not significantly different from that in the previous report (17 patients/month vs. 17.9 patients/month). 17 No patient with posterior circulation aneurysm underwent clipping in this cohort. A pterional keyhole approach was used except in 3 patients who developed brain herniation and received classic decompressive hemicraniectomy (1 [5%] vs. 2 [4.8%]; P = 0.967).…”
Section: Resultsmentioning
confidence: 86%
“…The rate and spectrum of postoperative complications in both the ANH group and the non-ANH group were consistent with a previous report from our institution. 17 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, if early prognosis of CV could be achieved to predict potential risks, optimized care and more effective distribution of healthcare resources might be made possible for these patients. There have been studies reporting on the connection between elevated Lp-PLA2 level and ACV in aSAH patients [19]. The associated morbidity and mortality of SCV could be higher than ACV.…”
Section: Discussionmentioning
confidence: 99%
“…Lipoproteinassociated phospholipase A2 (Lp-PLA2) is an available potential biomarker of inflammation in blood vessels [15][16][17][18]. It has been reported that in aSAH patients, elevated Lp-PLA2 level is related to angiographic cerebral vasospasm (ACV) [19]. However, whether Lp-PLA2 can predict the occurrence of symptomatic cerebral vasospasm (SCV) in aSAH patients is still unknown.…”
Section: Introductionmentioning
confidence: 99%